1994
DOI: 10.1093/oxfordjournals.annonc.a058801
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α, 5-FU and prednisone in metastatic renal cell carcinoma: A phase II study

Abstract: The assessed combination of IFN-alpha, 5-FU and prednisone is moderately active in MRCC, with response rates similar to those seen in patients on IFN-alpha monotherapy. The latter treatment approach seems preferable, as 5-FU-related toxicity (mucositis, cardiac toxicity) is averted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…22 In many studies the daily dose of INF-␣ has been low, less than 9 MU. 15,19,21 In this study, no objective responses were observed at doses less than 9 MU. Thus, it is possible that a threshold dose level is necessary for clinical benefit of IFN-␣.…”
Section: Table 4 Toxicity According To World Health Organization Gradmentioning
confidence: 52%
See 2 more Smart Citations
“…22 In many studies the daily dose of INF-␣ has been low, less than 9 MU. 15,19,21 In this study, no objective responses were observed at doses less than 9 MU. Thus, it is possible that a threshold dose level is necessary for clinical benefit of IFN-␣.…”
Section: Table 4 Toxicity According To World Health Organization Gradmentioning
confidence: 52%
“…1,5,7,17 Interferon-␣ has been as effective as a single agent or in combinations with interleukin-2, 8,14 vinblastine, 18 -20 and 5-fluorouracil. 21,22 The response rates have varied from 10% to 40%, most often from 15% to 20%. Hormone treatment is not effective in metastatic renal cell carcinoma, although some improvement in the quality of life of the patients can be achieved with medroxyprogesterone acetate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case calculation for each study based upon available response data following treatment with single agents or combinations of drugs administered. We assumed a response rate ≥ 25% to proceed with the further development of the respective schedule [ Creagan et al 1991 ; Zaniboni et al 1989 ; Haarstad et al 1994 ]. Prerequisite to resume schedule II was a CRP decline > 30% in patients experiencing stable disease or objective response on schedule I independently of whether stage two of a two stage flexible design may be achieved with schedule I [ Chen and Ng, 1998 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite the report of success with adjuvant hormonal therapy in this one case, conventional chemotherapy and hormonal agents have little effect on renal cell carcinoma (14). Similarly, the effect of biological immune modifying agents (eg, interferon), which have been reported to be of some value in the treatment of metastatic renal cell carcinoma (10,15,16), is unknown in the setting of gastrointestinal metastases.…”
Section: Case Presentationmentioning
confidence: 99%